Automation technologies and employment at risk: The case of Mexico - Alfonso Cebreros; Aldo Heffner-Rodríguez; René Livas; Daniela Puggioni (Banco de México, 2020)
Based on the methodology proposed by Frey and Osborne (2017), we use their estimates for the probability of automation of occupations together with household survey data on the occupational distribution of employment to provide a risk assessment for the threat that automation may pose to the Mexican labor market. We find that almost two thirds of total employment is at high risk of automation; slightly more than half if we only consider employment in the formal sector. We argue that, while these estimates provide a useful benchmark to start thinking about the impact that automation may have on the labor market, they should be interpreted with care as they are solely based on the technical feasibility to automate and do not reflect the economic incentives, or other factors such as the accumulation of human capital through education, to adopt automation technologies.
Keywords: E24; E26; F16; J21; J23; J24; J62; L23; L86; O33; O38; N16; 330; Automation; Human capital and occupational choice; Labor demand; Organization of production; Robots; Technological change